Manipulating NK cellular therapy from cancer to invasive fungal infection: promises and challenges - Oh, Bernice Ling Zhi; Chan, Louis Wei Yong; Chai, Louis Yi Ann (Frontiers in Immunology, 2023)
The ideal strategy to fight an infection involves both (i) weakening the invading pathogen through conventional antimicrobial therapy, and (ii) strengthening defense through the augmentation of host immunity. This is even more pertinent in the context of invasive fungal infections whereby the majority of patients have altered immunity and are unable to mount an appropriate host response against the pathogen. Natural killer (NK) cells fit the requirement of an efficient, innate executioner of both tumour cells and pathogens – their unique, targeted cell killing mechanism, combined with other arms of the immune system, make them potent effectors. These characteristics, together with their ready availability (given the various sources of extrinsic NK cells available for harvesting), make NK cells an attractive choice as adoptive cellular therapy against fungi in invasive infections. Improved techniques in ex vivo NK cell activation with expansion, and more importantly, recent advances in genetic engineering including state-of-the-art chimeric antigen receptor platform development, have presented an opportune moment to harness this novel therapeutic as a key component of a multipronged strategy against invasive fungal infections.